2008
DOI: 10.1016/j.pbb.2007.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Increased task difficulty results in greater impact of noradrenergic modulation of cognitive flexibility

Abstract: Previous research suggests that the noradrenergic system modulates certain types of cognitive flexibility. This study compared various doses of beta-adrenergic antagonists for their effect on cognitive flexibility in problem solving, and how task difficulty interacts with this effect, as well as the effect of beta-adrenergic antagonists on other tasks. Anagram task performance was compared in 72 subjects using a within-subject design for propranolol at 20 mg, 40 mg, 60 mg, and placebo in a double-blinded manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 38 publications
5
65
2
Order By: Relevance
“…However, in each of these studies involving anagrams, whereas performance on propranolol was significantly better than on ephedrine or nadolol, it did not significantly differ from placebo (Beversdorf et al, 1999;Beversdorf et al, 2002). Subsequent research demonstrated that propranolol is beneficial for network flexibility in problem solving particularly when the subject is struggling with the problem (Campbell et al, 2008), as would be expected since greater flexibility would be required for such situations where a greater network search is needed, and can actually impair performance when subjects are solving problems with ease (Campbell et al, 2008). However, in patients where noradrenergic activity is upregulated, such as in cocaine withdrawal, propranolol benefits performance on the simplest problems (Kelley et al, 2007).…”
Section: Noradrenergic System Stress and Cognitionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in each of these studies involving anagrams, whereas performance on propranolol was significantly better than on ephedrine or nadolol, it did not significantly differ from placebo (Beversdorf et al, 1999;Beversdorf et al, 2002). Subsequent research demonstrated that propranolol is beneficial for network flexibility in problem solving particularly when the subject is struggling with the problem (Campbell et al, 2008), as would be expected since greater flexibility would be required for such situations where a greater network search is needed, and can actually impair performance when subjects are solving problems with ease (Campbell et al, 2008). However, in patients where noradrenergic activity is upregulated, such as in cocaine withdrawal, propranolol benefits performance on the simplest problems (Kelley et al, 2007).…”
Section: Noradrenergic System Stress and Cognitionmentioning
confidence: 98%
“…Therefore, we examined the effects of pharmacological agents on network flexibility among individuals with ASD. Specifically, we examined the effect of propranolol on network flexibility in high-functioning adults with ASD using simpler verbal problem-solving tasks with which individuals without neurodevelopmental diagnoses would not be expected to benefit (Campbell et al, 2008). Due to their decreased flexibility of access to networks, we expected that individuals with ASD would have a selective performance benefit from propranolol.…”
Section: Noradrenergic System Cognition and Autismmentioning
confidence: 99%
“…Dysfunction in this system is thought to contribute to cognitive impairment in several neuropsychiatric disorders (e.g., attention-deficit/hyperactivity disorder, depression). Pharmacologic research has shown that cognition can be enhanced in both affected and unaffected persons by a-2-adrenergic agonists (e.g., guanfacine 34 ), b-adrenergic antagonists (e.g., propranolol 35 ), and norepinephrine transport inhibitors (e.g., atomoxetine 36 ). Further research on the role of the locus ceruleus norepinephrine system in cognitive aging is warranted.…”
Section: Figurementioning
confidence: 99%
“…Beta-blockers such as propranolol can help creative performance anxiety, and may have modest creativity benefits after acute administration. 66 Although there are case reports of propranolol causing depression and decreased libido, larger trials show no statistically significant increase in risk. 81 Benzodiazepines.…”
Section: Anxiolyticsmentioning
confidence: 99%